PERTAMBAHAN BOBOT BADAN HARIAN (PBBH) PADA AYAM LAYER STARTER GROWER YANG DIBERI RESVERATROL TEPUNG BIJI ANGGUR - Dyanovita AL Kurnia (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2019)
The purpose of this research was to examine the potention of using resveratrol of grape seed meal to increase average daily gain. The material used in this research are 60 layer poultry of 0-60 days. Resveratrol of grape seed meal devided in several level were p0 = commercial feed withouth Resveratrol of grape seed meal, P1 = commercial feed +  0.012 % Resveratrol of grape seed meal, P2 = commercial +  0.018 % Resveratrol of grape seed meal, P3 = commercial feed + 0.024 % Resveratrol of grape seed meal. Layer poultry were allotted to four level treatments randomly into P0, P1, P2, P3. Three replications each. The variables observed was of increase average daily gain. Data were analyzed by using Completely Randomized Design, when there was significant effect it was followed by Duncan’s Multiple Range Test. The result of this research showed that the use of resveratrol of grape seed meal doesn’t differ reality (P>0,05). But in the numeric showed P2 (12.85 ± 0.30) was better than all treatments p0 (12.27± 0.30), P1 (12.49 ± 0.08), p3 (12.71 ± 0.12).